Microstructures of bitumen observed by environmental scanning electron microscopy (ESEM) and chemical analysis using time-of-flight secondary ion mass spectrometry (TOF-SIMS). (1st October 2018) - Lu, Xiaohu; Sjövall, Peter; Soenen, Hilde; Andersson, Martin
Abstract: The aim of this study is to characterize structures induced on bitumen surfaces under analysis by environmental scanning electron microscopy (ESEM), and to examine possible contributing factors to the formation of their formation. Various bitumen samples are investigated, including soft and hard, as well as polymer modified bitumen. Chemical characterization is carried out by time-of-flight secondary ion mass spectrometry (TOF-SIMS), combined with principle component analysis (PCA). The study shows that, for soft bitumen, a tube pattern or worm structure is rapidly formed during ESEM analysis, but for hard bitumen, a longer exposure time is needed to develop a structure. The structures on the hard bitumen are also denser as compared to those on the soft bitumen. When sample specimens are deformed or stretched, the orientation of the created deformation is clearly reflected in the structures formed under ESEM, and for soft bitumen, the structure disappears overnight in vacuum but reappears with the same pattern upon repeated ESEM analysis. TOF-SIMS shows small but consistent chemical differences, indicating higher aliphatic and lower aromatic contents on the surface of the structured area compared to the unstructured area. Based on an estimated temperature increase on the bitumen surface due to the electron-beam irradiation, it is speculated that the ESEM-induced worm structure may be attributed to evaporation of volatiles, surface hardening and local expansion. In addition, under the electron-beam exposure, certain chemical reactions (e.g. breaking of chemical bonds, chain scission and crosslinking) may take place, possibly resulting in the observed chemical differences between the structured and unstructured areas.